Development of Quick Test Method for Soil pH, Nitrate, Phosphorus, and Potassium Combining Chemicals and Phone Cellular Application - Arief Hartono; Desi Nadalia; Dede Sulaeman (AGRIVITA, Journal of Agricultural Science, 2021)
Conventional soil analyses are time-consuming; therefore, the soil quick test (QT) method is needed. This study was to assess the accuracy of soil pH, N-nitrate, available phosphorus (P), and exchangeable potassium (K) analysis determined by the QT method developed by Akvo and calibrated with standard laboratory methods. The field research collected 131 soil samples, collected from horticultural lands in 4 regencies within East Java-Indonesia, started from February to August 2017. Soil analysis measured were soil pH, N-nitrate, available P, exchangeable K, textures, organic C, and CEC. The colorimetric-based QT method was performed on the soil sample extracted by Mehlich 1, and the color was developed by dipping strip test paper in supporting chemical solutions. A smartphone camera was used for the reading, and the results were directly displayed on the smartphone screen. The QT method’s calibration models were created by stepwise multiple linear regression involving the correlated soil chemical properties. The values of calibrated QT method (i.e. soil pH, N-nitrate, and available P) showed significant correlations with the values from the laboratory. However, the results suggested that the QT method developed by Akvo could be used for nitrate due to having a relatively high correlation with that of standard laboratory.